Wachstum und Zellteilung bei Urospora - Kornmann, P. (Helgoländer Wissenschaftliche Meeresuntersuchungen, 1966)
Hormiscia new-defined. There is only one way to clarify taxonomy and nomen- clature of the CodioIurn-Urospora-complex, and that is to compare cultures grown from the filamentous phase as well as from the unicellular stage. In this way correlative members in the life-history can be known, and the specifity or synonymy of the species is established. In the present study CodioIum gregarium A. B AUN, described 1855 from Helgoland, is shown to be the sporophyte of Hormiscia neglecta, a species that was hitherto not distinguished from Hor- miscia penicilliformis. The filaments of these two species grow consociated in the same locali- ties; they are similar in shape but differ clearly in the size of their anisogametes and sporo- phytes. In addition, only the sporophyte of Hormiscia neglecta has been found in the field, which is quite remarkable as the sporophyte of both species grew vigorously in culture. The name Hormiscia is applied here to the anisogamous species which are filamentous when cultivated at 15 ° or 50 C. Urospora is restricted only to species without gametes; they are filamentous at low temperature and modify into dwarf-plants at 150 C. The Codiolmn-phase originates from asexual biflagellate zoospores of this stage.